Ce-hydroxamate metal–organic frameworks for photocatalytic H2 generation. Issue 97 (17th November 2022) - Feng, Xuan; Li, Wenying; Yang, Lei; Song, Ting; Xia, Zhaoming; Lai, Qiuxue; Zhou, Xuemei; Xiao, Hai; Liu, Chong
Abstract : Exploring the rich coordination chemistry of cerium, two new hydroxamate MOFs are reported, featuring distinct band structures and photoelectrochemical properties for H2 generation. Abstract : Exploring the rich coordination chemistry of Ce, here we report two new entries in the emerging category of hydroxamate-based metal–organic frameworks (MOFs). The two Ce-hydroxamate MOFs exhibited different band structures and photoelectrochemical properties based on their respective coordinative environments and overall structures, leading to varied H2 generation performances.